1999
DOI: 10.1007/s000110050499
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA decay is accelerated by an inhibitor of p38-mitogen-activated protein kinase

Abstract: Specific mRNA destabilization represents an important and novel site of action for the cytokine suppressive effects of p38 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 17 publications
1
71
0
Order By: Relevance
“…Indeed, we observed that the expression of TNF-␣ and members of the IL-1 family was partially reduced by SB203580 treatment. It remains to be determined whether these inhibitory effects are transcriptional or posttranscriptional, because recent experiments demonstrate that inhibition of p38 MAPK can lead to specific mRNA destabilization (47,48). One possible explanation is that p38 MAPK inhibition interfered with the normal process of DC maturation by affecting proinflammatory cytokine expression through NF-B negative modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that the expression of TNF-␣ and members of the IL-1 family was partially reduced by SB203580 treatment. It remains to be determined whether these inhibitory effects are transcriptional or posttranscriptional, because recent experiments demonstrate that inhibition of p38 MAPK can lead to specific mRNA destabilization (47,48). One possible explanation is that p38 MAPK inhibition interfered with the normal process of DC maturation by affecting proinflammatory cytokine expression through NF-B negative modulation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF␣ expression is activated mainly by the transcription factor NF-B and by the MAP kinase (MAPK) pathways (the ERK, JNK, and p38 MAPK pathways). Recent studies have shown that the p38 MAPK pathway in particular plays an important role in posttranscriptional regulation that leads to mRNA stabilization (41). The p38 MAPK pathway also strongly induces and activates TTP, which down-regulates TNF␣ (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Because the 3Ј UTR of IL-2 contains AREs, and IL-2 mRNA stability is the same in both C57BL/6 and DBA/2 splenocytes, altered Th2 cytokine mRNA stability between these two strains may involve modulation by some additional mechanism, perhaps differential expression of Th1-or Th2-specific trans-acting factors. In addition to AREs, the activities of p38 MAP kinase and tristetrapolin have been shown to modulate the half-lives of short-lived transcripts (42)(43)(44)(45). It is possible that p38 and tristetrapolin could modulate mRNA stability and that differential expression or activation of these molecules might account for altered Th2 cytokine mRNA stability in DBA/2 and C57BL/6 splenocytes.…”
Section: Discussionmentioning
confidence: 99%